The pattern of thyroid function abnormalities seen among apparently healthy pregnant women in Enugu, Nigeria - Anthony U Mbah; Louis O Ekpechi (International Journal of Medicine and Health Development, 1999)
There have been conflicting reports regarding the biochemical status of thyroid function in normal pregnancy. The objective of the current study, therefore, was to detect biochemical thyroid dysfunction among healthy pregnant women in Enugu and, if found, to elucidate the pattern.One hundred and sixty three apparently healthy women with normal pregnancies who attended routine antenatal clinic in a general maternity hospital in Enugu, Nigeria from September 6 to October 18, 1994 were consecutively recruited into the study. Each of the subjects exhibited an aberrant value in one or more of the biochemical indices studied. In terms of the biochemical status of their thyroid function, 95 (58.3%) of all the pregnant women had both TSH and FT4 values within the laboratory reference ranges and so had features compatible with euthyroidism. The remaining 68 (41.7%) had some aberration in either the TSH or the FT4, or in both. Forty one (25.2%) had biochemical features suggestive of stage 2 hypothyroidism (high TSH + normal FT4), 19 (11.7%) had features indicative of stage 3 hypothyroidism (high TSH + low FT4), 3 (1.8%) had TSH and FT4 values within hyperthyroid ranges while 8(4.9%) had indeterminante status of thyroid function. It is concluded that patterns of biochemical indices of thyroid function compatible with primary hypothyroidism appear to be quite common among apparently healthy pregnant women in Enugu. However, biochemical hypothyroidism in pregnancy is more likely due to gestation than due to thyroid disease if serum TSH concentration is less than 11mU/L.